Pentingnya Membangun Karkter untuk Menghadapi Era Gen Z pada Muatan Pembelajaran IPS Madrasah Ibtidaiyah - Aisyah Alya Alfiyyah; Fairuzi Fairuzi; Oman Farhurohman (Lembaga Pengembangan Kinerja Dosen, 2025)
Madrasah Ibtidaiyah plays an important role in shaping the character of the younger generation, especially facing the challenges of generation Z who have grown up in the digital era. This generation has characteristics such as visual orientation, high technology involvement, and learning patterns that demand interactivity. Social studies education at Madrasah Ibtidaiyah is a strategic forum for instilling Islamic character values ​​such as integrity, cooperation and social responsibility. The development of an integrated and innovative curriculum, involving a thematic approach that is relevant to the needs of the times, is needed to eliminate barriers between scientific disciplines, thereby providing holistic learning. Learning strategies based on moral values, technology and collaboration can increase the effectiveness of character education. Teachers as curriculum developers play a vital role in compiling, implementing and evaluating teaching methods that suit the needs of generation Z, whether through Student-Centered Learning, Visual-Based Learning, or Flipped Classroom approaches.This research emphasizes the importance of collaboration between teachers, students, and technology in realizing social studies education that is able to create a generation that is critical, moral, and ready to face global challenges without losing its Islamic identity. With this approach, madrasahs are able to produce the nation's next generation who are superior in character and competence.